2023
DOI: 10.3389/fped.2023.1127659
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of children with cystic fibrosis screen positive, inconclusive diagnosis/CFTR related metabolic syndrome

Abstract: BackgroundSome infants undergoing newborn screening (NBS) tests have inconclusive sweat chloride test (SCT) results that lead to the designation of Cystic Fibrosis Screen Positive, Inconclusive Diagnosis/CFTR-related metabolic syndrome (CFSPID/CRMS). Some proportion of them transition to a CF diagnosis, but no predictive markers can stratify which are at risk for this transition. We report single-center outcomes of children with CRMS.MethodsWe retrospectively identified all infants born in Alabama from 2008 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Research exploring the phenotypic expression of infants diagnosed with CFSPID has unveiled decreased levels of immunoreactive trypsinogen (IRT) and sweat chloride compared to confirmed CF cases. [32,33]. Terlizzi and Dolce (2023) found that CFSPID patients exhibited more variability in sweat test values than CF infants.…”
Section: Neonatal Screeningmentioning
confidence: 99%
“…Research exploring the phenotypic expression of infants diagnosed with CFSPID has unveiled decreased levels of immunoreactive trypsinogen (IRT) and sweat chloride compared to confirmed CF cases. [32,33]. Terlizzi and Dolce (2023) found that CFSPID patients exhibited more variability in sweat test values than CF infants.…”
Section: Neonatal Screeningmentioning
confidence: 99%
“…The incidence of CRMS/CFSPID varies internationally depending on the population and algorithms used. It is unclear how many of these children will go on to develop CF or a CFTR-related disorder [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]: the latter is defined as “…clinical conditions that are recognised to be associated with abnormality of the CFTR gene but are not CF” [ 7 ]. Depending on how EGS is used ( Box 1 ), it could result in more children with CF being missed (undiagnosed following NBS) but fewer children with CRMS/CFSPID being identified (a specific approach), or fewer children with CF being missed but more children with CRMS/CFSPID being identified (a sensitive approach) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of CRMS/CFSPID varies internationally depending on the population and algorithms used. It is unclear how many of these children will go on to develop CF or a CFTR-related disorder [8][9][10][11][12][13][14]: the latter is defined as ". .…”
Section: Introductionmentioning
confidence: 99%